The Impact of the Interaction between Parents, Employment Status, Income, and Education on the Risk of Stunting in Sungai Landas Village - Setiawan, Muhammad Irwan; Rahman, Fauzie; Khadafi, Muhammad Zainal; Rahma, Amelia; Nayla, Nurul Alifa; Hayyana, Nawwara; Wati, Ratna Mulia (Miracle Journal of Public Health, 2025)
Stunting is a chronic nutritional problem that affects the growth and development of children. The results of community diagnostics that have been carried out from January to February 2025 in Sungai Landas Village show data that 30% of children aged 0-60 months are stunted. This study aims to analyze the relationship between employment status, income, and parental education on the incidence of stunting in Sungai Landas Village, Karang Intan District, Banjar Regency. This study used a cross-sectional design with a sample of 30 respondents from Sungai Landas Village who have children aged 0-60 months. Data were collected through questionnaires and anthropometric measurements and then analyzed using Fisher's exact test with a 95% confidence level. The results showed that there was no significant relationship between parents' employment status (p=0.329) and parents' income (p=1.0). There was a significant relationship between parents' education level (p=0.030) and the incidence of stunting. Parental education plays an important role in understanding nutrition, which affects parenting and children's food intake. Therefore, increasing community-based nutrition education, especially for parents, needs to be the focus of stunting prevention efforts.